PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI SUDAN SELATAN 2022-2023 - Azara, Fathia Vella; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study analyzes the role of the World Food Programme (WFP) in dealing with the food crisis in South Sudan. This study is interesting to discuss because the food crisis in South Sudan has become one of the most serious humanitarian issues due to a combination of prolonged conflict, climate change, and limited infrastructure. The World Food Programme (WFP) as an international organization under the auspices of the UN plays a strategic role in efforts to overcome the crisis. This study aims to analyze what WFP has done to deal with the food crisis in South Sudan. This research is a qualitative research with data collection through library research and internet research. The theory used is the theory of the role of international organizations. This study uses a group analysis level that has the essence of understanding, studying, and evaluating the behavioral attitudes of a group with non-state actors who already have international coverage. The research findings show that WFP is not only acting as a provider or emergency food assistance, but also a development actor that promotes long-term food security.Programs such as the Integrated Rapid Response Mechanism (IRRM), Food Assistance for Assets (FFA), and the School Feeding Programme show how WFP distributes aid effectively while building local capacity. Despite facing funding challenges, WFP remains committed to reducing the impact of the food crisis. In addition, WFP is also a channel for other countries that want to provide assistance. Keywords: WFP, food crisis, South Sudan, international organizations,